Laser ablation synthesis of gold nanoparticle to enhance the ﬂuorescence properties of graphene quantum dot - Sadrolhosseini, A. R.; Suraya A. R.,; Suhadi S.,; Nezakati, Hossein * (Laser Institute of America, 2019)
Gold nanoparticles were fabricated in the graphene quantum dots solution using the laser ablation technique. In order to control the particle size and concentration of nanoparticles, the ablation time is changed from 5 to 25mins. UV–visible spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscopy, and ﬂuorescence spectroscopy were used to characterize the prepared samples. Consequently, the localized surface plasmon resonance absorption peaks appeared in the range of 515.9–520nm, while the peak which appeared at 319.8 is related to graphene quantum dots. The gold nanoparticles were formed in a spherical shape, which have had interaction with carboxyl and hydroxylic groups. The particle size was in the range of 28.29–11.74nm, which decreased with an increase in the ablation time. The excitation wavelength was about 300nm, and the emission wavelength appeared at 432.23nm. As a result, the intensity of the emission increased with an increase in the ablation time, while the particle size decreased due to the plasmonic property of gold nanoparticles, and the quantum yield is in the range of 38.208%–55.068%